The role of Surfacant Protein D in the control of human helminth infections - Baker, Zoe (Division of Immunology, 2021)
Lung produced surfactant protein D (SP-D) is essential for both homeostasis and as an innate immune opsonin. In the project presented here, we aimed to translate data recently published by our group, which demonstrated that SP-D contributes to protection against murine parasitic nematode infections, to human work. In the first part of this study, we determined whether individuals exposed to helminths have altered serum SP-D in comparison to unexposed individuals, through analysis (ELISA and Western Blot) of bio banked samples in 2 clinical cohorts from South Africa. Secondly, we aimed to identify if SP-D influences the magnitude of anti-nematode responses in human immune cells (type 2 innate lymphoid cells, monocytes and macrophages) through in vitro cell work and flow cytometry. Our findings indicated an association between serum SP-D and exposure to helminths that have a lung migration stage as part of their life cycle (Ascaris spp and Toxocara spp). Furthermore, in vitro analysis demonstrated that human immune cells primed with SP-D might have an altered response to helminth antigen. These findings point toward the need for further investigation into the novel role of SP-D in the control of human helminth infections in the context of immune physiology, as a biomarker and eventually treatment option.